Bước đầu nghiên cứu thành phần hóa học cây niệt gió (Wikstroemia indicai. C. A. Mey, Thymelaeaceae) - Thùy, Trần Văn; Tuấn, Dương Anh; Tuyến, Nguyễn Văn; Anh, Bùi Kim; van Puyvelde, Luc (Vietnam Journal of Chemistry, 2014)
Two lignans, (+)-lariciresinol (2), (-)-secoisolariciresinol (3), the flavonoid tricin (1) and the  bis-coumarin 4 were isolated from the dichloromethane extract of the stem bark of Wikstroemia indica C. A. Mey, Thymelaeaceae. The structures of these compounds were determined by spectroscopic methods.